Index (Zbornik radova međunarodnog teološkog skupa KBF-a u Splitu, 2018)
The author starts from the fact that the debate about governance and authority, i.e. sovereignty of governance in 21st century is impossible without a precise definition of social changes and new historical situation we live in. The authority of governance has to be viewed considering to what extent the governance is contemporary. Having defined the starting point, the author analyzes the social, political, economic and cultural moment in Croatia. On the basis of his analyses and observations he concludes that nowadays the state authority in general, and also the state authority in Croatia, is not sovereign, although it is written so in its Constitution. There are more and more super national institutions and organizations which restrict it. The concept of the European Union, which Croatia wants to join, aims at creating a super national state in which the members lose a great part of their sovereignty in various areas. Therefore Tomac holds that it is necessary to think twice and to make competent arguments what Croatia gets and what it loses entering the Union, he lists some current ultimatums that the world persons in power set to Croatian people (disintegration of Croatian national identity, falsification of history, creation of soft Balkan union, etc), he describes how Croatian politics does not protect its national interests, sells off the banks, media and resources; it hurtles toward new integrations without learning from its own historical errors. A fateful question is put: are we going to survive as a nation and state in the age of globalism, which as a new ideology wants to rule over people and nations by its totalitarianism and to disintegrate the traditional, national, cultural and spiritual values in all fields of life. Globalism is a new form of 21st century capitalism which takes over most of national states’ authorities to build up a world super state, it wants a complete control over the person and his/her transformation into a weak and dependant being, without will or identity. In that way man becomes a victim of new slavery. The author points at that danger and wants to oppose it with all his might.